Finding funds, sharing success - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Who do you turn to when you have a promising project and are looking for an appropriate funder? Both ENDS (Environment and Development Service) may be what you need. They act as 'brokers' for projects - in this role they also aid funders who are...